Searching for new mTOR kinase inhibitors: Analysis of binding sites and validation of docking protocols - Stary, Dorota; Nepovimova, Eugenie; Kuca, Kamil; Bajda, Marek (Chemical biology & drug design, 2023)
The mammalian target of rapamycin (mTOR) is an important biological target for development of novel anticancer drugs and potential antiageing agents. Therefore, many scientific groups search for mTOR kinase inhibitors. Herein, we present structure-based approach which could be helpful in the studies on new bioactive compounds. Method validation was preceded by structural analysis of ATP catalytic cleft and FRB domain. In silico studies allowed us to point crucial amino acid residues for ligand binding and develop optimal docking protocols. The presented methodology could be applied for design and development of potential mTOR kinase inhibitors.
Keywords: Binding Sites; Sirolimus; protinádorové látky; Antineoplastic Agents; sirolimus; Protein Kinase Inhibitors; inhibitory proteinkinas; vazebná místa